Genotoxic Potential of Nanoparticles: Structural and Functional Modifications in DNA - Shukla, Ritesh K; Badiye, Ashish; Vajpayee, Kamayani; Kapoor, Neeti (Frontiers in Genetics, 2021)
The rapid advancement of nanotechnology enhances the production of different nanoparticles that meet the demand of various fields like biomedical sciences, industrial, material sciences and biotechnology, etc. This technological development increases the chances of nanoparticles exposure to human beings, which can threaten their health. It is well known that various cellular processes (transcription, translation, and replication during cell proliferation, cell cycle, cell differentiation) in which genetic materials (DNA and RNA) are involved play a vital role to maintain any structural and functional modification into it. When nanoparticles come into the vicinity of the cellular system, chances of uptake become high due to their small size. This cellular uptake of nanoparticles enhances its interaction with DNA, leading to structural and functional modification (DNA damage/repair, DNA methylation) into the DNA. These modifications exhibit adverse effects on the cellular system, consequently showing its inadvertent effect on human health. Therefore, in the present study, an attempt has been made to elucidate the genotoxic mechanism of nanoparticles in the context of structural and functional modifications of DNA.